PENGARUH KINERJA KEUANGAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2017-2021 - Etnandia Tri Wulandari; Evaliati Amaniyah (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
The purpose of this study is  to determine the financial performance of financial distress in food and beverage subsector companies listed on the Indonesian stock exchange for the 2017-2021 period.  The selected p opulation was the  food and beverage subsector  of 32  companies, the sample was selected using the purpose sampling method  as many as 22 companies that were sampled in the study. The variables used in this study are liquidity ratio,  profitability ratio,  leverage  ratio, and  activity ratio  as independent variables, financial distress as dependent variables.   The data analysis technique used in this study is multiple linear regression analysis, with hypothesis testing of t statistical tests and f statistical tests with SPSS (statistical product and service solutions) application tools. The results of this study prove that: (1) The ratio of  likuidity has a positive and significant effect on financial distress (2) The ratio of  profitability has a positive and significant effect on financial distress (3) The leverage ratio  has a negative and significant effect on financial distress (4)  Ratio   Activity has a positive and significant effect on financial distress.